THE EFFECT OF DIET PATTERNS, PARENTING METHODS, AND PHYSICAL ACTIVITY ON THE NUTRITIONAL STATUS OF TODDLERS AT BUNGKU PUBLIC HEALTH CENTER - Panca Radono; Idawati Hasyim; Retno Palupi Yonni Siwi; Nurwijayanti (Universitas Karya Husada Semarang, 2024)
The high incidence of malnutrition in toddlers is caused by an unbalanced diet, poor parenting, and a lack of physical activity, which has an impact on the suboptimal growth and development of toddlers. The purpose of this study was to determine the effect of diet, parenting, and physical activity on nutritional status in toddlers. This study used a correlational analytical design with a cross-sectional approach. The population consisted of 53 respondents with a sample of 47 respondents, selected using a simple random sampling technique. Data were collected through the use of questionnaires, and the analysis used multivariate regression statistical tests. The results showed that most respondents had a poor diet (70.2%), almost all applied democratic parenting (87.2%), most did toddler physical activities well (95.8%), and the majority had poor nutritional status (74.4%). There was a significant relationship between diet patterns and nutritional status of toddlers at the Bungku Health Center, Morowali Regency (p = 0.001 <0.05). However, no significant relationship was found between parenting methods (p = 0.434 > 0.05) and toddler physical activity (p = 0.682 > 0.05) with the nutritional status of toddlers in the same location. Diet patterns, parenting methods, and physical activity are among the factors that influence nutritional status in toddlers, thus having an impact on child growth and development.